PELAKSANAAN PEMBELAJARAN LINTAS MINAT DAN PRESTASI BELAJAR SISWA KELAS X MIA 1 MAN 2 PONTIANAK - Safitri, Mardiana; Parijo, Parijo; Khosmas, F Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe tittle of this thesis is: The Implementation Of Learning Cross-Interest And Studentsâ€™ Learning Achievement Of Class X MIA 1 MAN 2 Pontianak. The sub-problems in this study are 1. how is the meaning of learning cross-interest 2. how is the implementation of learning cross-interest in the students of class X MIA 1 MAN 2 Pontianak 3. How do studentsâ€™ achievement of class X MIA 1 MAN 2 Pontianak on subjects cross-interest. This research uses qualitative approach with descriptive method. To collect the data, the writer uses observation, interviews and documentation studies with data collection tool of observation guides, interview guides, notebooks and archives. The informants in this study are the subjects of teachers cross-interest and students of class X MIA 1. From the results of this study indicates that the subject teachers have implemented learning cross-interest well, both the way of learning and learning tools required to exist. From the implementation of learning that has been so adequate that supported by facilities and teacher and established a good interaction between teachers and students, so the purpose of learning the students on across interest can be achieved by subject that has been given.Keywords: Implementation of Learning, Across Interest, LearningAchievemetÂ